Critical success factors of public health sponsorship in Australia. (17th December 2018) - Sung, Billy; Phau, Ian; Cheah, Isaac; Teah, Kevin
Abstract: Public health sponsorship is a unique phenomenon in Australia. The current research examines the critical success factors of Western Australian Health Promotion Foundation's (Healthway) sponsorship program, Australia's largest public health sponsorship program. Using stakeholder interviews and expert observational studies, two studies present five key success factors: (i) effective segmentation and targeting of health messages; (ii) collaboration between Healthway and partnering organization to leverage sponsored events; (iii) displacement of unhealth sponsorship; (iv) use of leveraging strategies to raise awareness of health messages; and (v) environmental changes that facilitate behavioural change. The current research provides insights into how and why sponsorship is an effective public health promotion tool.